Mental health in basic education teachers during the COVID-19 pandemic: from Burnout to the solution - Huamán Chura, Katthia Emily (2021)
The pandemic caused by the new coronavirus (COVID-19) has generated a radical change in the teaching method of basic education teachers, as they have become possible victims of the Burnout syndrome due to the overload of functions. This article aims to review this reality in the current literature, although the number of articles on the subject is limited. The purpose of this research is to provide a broader overview of the mental health situation of basic education teachers during the COVID-19 pandemic and try to propose some alternative solutions, including enhancing coping skills and improving remote workplace dynamics